Manifesto: A Different Jazz Studies - Jazz Research Journal Editorial Board (Jazz Research Journal, 2023)
The editorial board of Jazz Research Journal collectively authored this statement over a number of months in 2021 and 2022. We consider it a necessary and long overdue intervention into the field of jazz studies. The statement describes the jazz studies we want to see.